2004
DOI: 10.1002/cbf.1193
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine increases extracellular levels of 3‐methoxy‐4‐hydroxyphenylglycol in cultured COLO320 DM cells

Abstract: Fluoxetine (Prozac) is a serotonin reuptake inhibitor. It increases extracellular levels of serotonin and is used in relieving the depressive symptoms of cancer patients. It has been reported that the drug may enhance the growth of certain cancer cells. This study investigates whether fluoxetine enhances the growth of a human colon cancer cell line (COLO320 DM) and if it affects the extracellular levels of serotonin or its metabolite, 5-hydroxyindole-3-acetic acid (5-HIAA) and other monoamines and metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…33 It has been demonstrated that fluoxetine can inhibit 11,35 or activate ERK1/2, 36,37 depending on cell type and cellular context. It has also been reported that FLX inhibited proliferation in cancer cell lines, including prostate carcinoma cells, 20 colon carcinoma, 38,39 and induced apoptosis in Burkit Lymphoma cells, 40 rat glioma and human neuroblastoma cell lines. 41 However, normal peripheral blood mononuclear cells and tonsil B cells, whether resting or stimulated into cycle, were largely resistant to FLX-induced cell death, 40 which makes FLX a potentially welltolerated agent with anti-cancer action.…”
Section: Research Papermentioning
confidence: 89%
See 1 more Smart Citation
“…33 It has been demonstrated that fluoxetine can inhibit 11,35 or activate ERK1/2, 36,37 depending on cell type and cellular context. It has also been reported that FLX inhibited proliferation in cancer cell lines, including prostate carcinoma cells, 20 colon carcinoma, 38,39 and induced apoptosis in Burkit Lymphoma cells, 40 rat glioma and human neuroblastoma cell lines. 41 However, normal peripheral blood mononuclear cells and tonsil B cells, whether resting or stimulated into cycle, were largely resistant to FLX-induced cell death, 40 which makes FLX a potentially welltolerated agent with anti-cancer action.…”
Section: Research Papermentioning
confidence: 89%
“…Concerns were raised about the tumor-promoting potential of FLX when it was reported that clinically relevant doses of FLX accelerated the growth of mammary tumors in rodents. 43 However, later studies revealed an opposite effect, showing that FLX inhibits proliferation of several cancer cell lines, 20,[38][39][40] including also MCF-7 mammary cancer cells. 44 The mechanism of antiproliferative action of FLX on cancer cells is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Newer studies using electron microscopy immunochemistry proposed serotonin as a carcinogenic substance in colon cancer differentiation [74]. Furthermore, a decreased metabolic activity and growth of cultured human colorectal carcinoma after treatment with SSRIs was reported [75]. Recently, a large epidemiological study described a reduced risk of colorectal cancer after daily intake of SSRIs compared with non-users of such antidepressants [76].…”
Section: Serotonin In Gi Diseasementioning
confidence: 97%
“…The anti-tumor proliferative effects of FLX [40,56,92,93] have been related to different causes, such as delays in cell-cycle progression by inhibiting DNA synthesis and also to a possible binding directly to DNA via groove mode and high attraction force [58,[87][88][89][90]94] . On a molecular level, FLX was shown to arrest breast tumor cells at G0/G1 phase by disrupting skp2-CKS1 assembly, which is required to enable cell cycle progression [91] .…”
Section: Flx Reduces Preneoplastic Lesions Acting On Colonic Microenvmentioning
confidence: 99%